2017
DOI: 10.1007/s11060-017-2504-y
|View full text |Cite
|
Sign up to set email alerts
|

Neuro-oncology family caregivers’ view on keeping track of care issues using eHealth systems: it’s a question of time

Abstract: Primary brain tumors (PBTs) are rare but have a great impact on both patient and family caregiver wellbeing. Supporting caregivers can help them to continue their caregiving activities to maintain the patients’ best possible level of quality of life. Efforts to improve PBT caregiver wellbeing should take into account country- or culture-specific differences in care issues and supportive care needs to serve larger caregiver groups. We aimed to explore PBT caregivers’ satisfaction with the current supportive car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 29 publications
(27 reference statements)
0
14
0
3
Order By: Relevance
“…This was followed by an improvement for both caregivers and patients. Potential explanations for these findings warrant further consideration, for example, (a) the high caregiver rating for anxiety and depressive symptoms during oncological treatment corresponds to the fact that seven patients died, possibly attesting to a distressing end-of-life period; (b) the caregivers identified as highly engaged in the course of the disease and treatment of the patients are challenged by a lack of energy and difficulties in managing the patients' limitations, for example, cognitive changes (Piil et al, 2018); and, notably, (c) the caregivers' mood was strongly connected to the patients' prevalence and severity of symptoms (Boele, Given, et al, 2017;Boele, van Uden-Kraan, et al, 2017). Close analysis of MDASI-BT results showed that patients suffered from the highest number of symptoms (5.3 symptoms) at Week 30, when the most prevalent symptoms were fatigue, change in bowel pattern, remembering things, lack of appetite, and feeling sad and being distressed.…”
Section: Discussionmentioning
confidence: 99%
“…This was followed by an improvement for both caregivers and patients. Potential explanations for these findings warrant further consideration, for example, (a) the high caregiver rating for anxiety and depressive symptoms during oncological treatment corresponds to the fact that seven patients died, possibly attesting to a distressing end-of-life period; (b) the caregivers identified as highly engaged in the course of the disease and treatment of the patients are challenged by a lack of energy and difficulties in managing the patients' limitations, for example, cognitive changes (Piil et al, 2018); and, notably, (c) the caregivers' mood was strongly connected to the patients' prevalence and severity of symptoms (Boele, Given, et al, 2017;Boele, van Uden-Kraan, et al, 2017). Close analysis of MDASI-BT results showed that patients suffered from the highest number of symptoms (5.3 symptoms) at Week 30, when the most prevalent symptoms were fatigue, change in bowel pattern, remembering things, lack of appetite, and feeling sad and being distressed.…”
Section: Discussionmentioning
confidence: 99%
“…Respecto al primero, Yoo et al (2019), encontró la necesidad manifestada de recibir asesoramiento y apoyo durante el proceso salud-enfermedad, en el diagnóstico, tratamiento y hospitalizaciones. En cuanto al segundo, Somanadhan y Larkin, (2016), Landfeldt et al (2018), Uttley et al (2018), Magliano et al (2014), Boele et al (2017) y otros, enfatizaron que los cuidadores afrontan la situación sin apoyo psicológico y de manera empírica, obligándose a permanecer con una actitud positiva para mantener unida a la familia, lo cual se constituye en todo un desafío y una lucha emocional en la aceptación del diagnóstico y búsqueda de opciones de tratamiento. Este vacío en el trabajo multidisciplinar y el de Enfermería, establece otra brecha que el cuidado puede estrechar por medio de una conexión efectiva entre el cuidador y demás profesionales de la salud (JAE_v79n5.pdf, s. f.).…”
Section: Fuente: Autoría De Los Investigadoresunclassified
“…Por otro lado, las necesidades sanitarias se evidenciaron en diferentes perspectivas, desde la que resalta el soporte que proporciona el equipo multidisciplinario, como lo afirmó Soares et al (2016) y Boele et al (2017), como la que alerta sobre la insensibilidad, desconsideración, falta de empatía y conocimientos, como lo ratifican Bose et al (2019) y Rice et al (2019). El abordaje diagnóstico de la enfermedad fue descrito como una experiencia complicada, por la manifestación de los síntomas y ejecución de múltiples pruebas que en diversos casos causaron agotamiento e incertidumbre (Palacios-Ceña et al, 2018) y (Baumbusch et al, 2019).…”
Section: Fuente: Autoría De Los Investigadoresunclassified
See 1 more Smart Citation
“…There are intervention and/or support programs that have been positively evaluated [ 12 - 15 ], although most of them are based on in-person training. However, research has shown that many caregivers underutilize the supports available to them and instead try to handle everything by themselves [ 16 , 17 ]. The barriers that hinder access to in-person support programs include a lack of coordinated home care services [ 18 ], the multiple occupations and intensive dedication required by family care [ 19 ], geographical or transportation limitations, and the caregivers’ own health problems [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%